Integrative analysis reveals RNA G-quadruplexes in UTRs are selectively constrained and enriched for functional associations - David S. M. Lee (Nature Portfolio, 2020)
G-quadruplexes (G4s) are secondary structures that can form in both DNA and RNA from guanine-rich sequences which are enriched in untranslated regions (UTRs). Here, Lee et al. find that putative G4-forming sequences are evolutionarily constrained, enriched for RNA-binding protein interactions and enriched for disease genetic associations.